Ocio y senderismo literario por la Sierra de Guadarrama. Del puerto de Tablada con el Arcipreste de Hita a «La Senda de los Poetas» - Tejero Robledo, Eduardo (Didáctica. Lengua y Literatura, 2007)
In this paper, a literary trip to the Sierra de Guadarrama is offered to parents, teachers, hikers, ramblers and even elderly people. The poetic significance this privileged space has held for centuries is explained diachronically. With the pretext of appealing the interests of schools in leisure and social studies, we begin a pedagogic or didactic journey with a line of romance de cordel and with the great poets of our Literature as companions on our way. Cet article prétend proposer aux parents, aux professeurs, aux randonneurs, aux excursionnistes et même aux personnes âgées un voyage littéraire à travers la Sierra de Guadarrama. Il présente de manière diachronique la charge poétique dont cet espace privilégié a bénéficié pendant des siècles. Sous prétexte de loisirs et de connaissance de l’environnement, qui sont d’intérêt scolaire, nous entreprenons un voyage pédagogique ou didactique avec, comme compagnons de route, les grands poètes de notre Littérature.